Evaluación de efluentes del camal municipal de la localidad de Bellavista - Cárdenas Marcelo, Mendy Mariola (2014)
Technically the Animal sacrifice centers for human consumption or slaughterhouse have been defmed as a unit service of hygiene and public health. Many countries have already begun to address this problem and have begun the construction of modero facilities with special characteristics, whose purpose is to solve severa! problems by reducing maximum or suppression of the disadvantages inherent in the operations to realize. In many cases these centers of animal sacrifice does not have the technical and health conditions suitable for the development of the activity, which increases the risks of contamination of the products that every day are manipulated; inside this context by means of the present Monographic W ork, the evaluation had as general aim realize of effluent of the municipal halter of Bella vista locality of the San Martín region in order to determine the environmental impacts and possible effects to the Public Health of the city mainly as well as the environmental components and depending on it to raise corrective and 1 or preventive policies for the improvement of the provision of services and health of the city. The used methodology was based on the summary of the existing information and the check of the same one on the place. Since part of the obtained results establishes that the negative situation of the Municipal Halter of Bellavista province is owed principally to the current location ofthe existing halter (road to Bellavista income), the existing facilities do not have the appropriate infrastructure for the handling and treatment of red meats, suitability characteristics do not exist, it does not have a system of treatment of wastewater from the current slaughterhouse, causing in this way a contaminant for the population, the state of health of the wastewater is located in a negative situation, which is cast directly the Huallaga river. Finally it is needed to make lasting and operatively viable the implementation of all the measures of environmental managing before mentioned, it is necessary that the personnel of the Municipal Halter is conscious of the advantages that it represents to assume them adequately. The benefit will be for both the performance of their work and the place where they work, as for the improvement ofthe level of quality life ofthe inhabitants. Todo this, it should complement the program of integrated waste management module with a training and awareness to all the personnel working in the slaughterhouse. Between the contents, include the characteristics of implementation, operation and performance of each measure of management and/or treatment unit, the procedural details for the implementation of the program and its benefits in all the orders.